If I should die - Rouner, Leroy S. (Notre Dame, Ind. : University of Notre Dame Press, 2001)
"The contributors to If I Should Die offer the reader compelling personal, philosophical, and historical views on questions about death."--BOOK JACKET.
A short while towards the sun / Rita Rainsford Rouner -- Death and the believer : the end is where we start from / Peter John Gomes -- Is there life after death? / Jürgen Moltmann -- If I should die before I am awakened : Buddhist reflections on death / Malcolm David Eckel -- A rose for the Buddha : in response to David Eckel / Brian W. Jorgensen -- Why people in stories choose mortality when they could have immortality / Wendy Doniger -- The vague hope of immortality / John Lachs -- "This tablet, which itself will quickly perish" / Aaron V. Garrett -- Metaphorical immortality : some Platonic reflections / David L. Roochnik -- The meanings of life / David Schmidtz.
Includes bibliographical references and indexes.
Keywords: Death -- Religious aspects; Immortality (Philosophy)